Effectiveness of fast mapping to promote learning in schizophrenia - Korenic, Stephanie A.; Nisonger, Sarah J.; Krause, Benjamin W.; Wijtenburg, S. Andrea; Hong, L. Elliot; Rowland, Laura M. (Schizophrenia research. Cognition, 2016)
Fast mapping (FM), a process that promotes the expeditious incidental learning of information, is thought to support rapid vocabulary acquisition in young children through extra-medial temporal lobe (MTL) regions. A recent study suggested that patients with MTL damage resulting in profound amnesia were able to learn novel word–image associations using an FM paradigm. The present study investigated whether FM would be an effective strategy to promote learning for individuals with schizophrenia, a severe mental illness associated with compromised MTL functionality. Twenty-five patients with schizophrenia and 27 healthy control subjects completed trials of incidental FM encoding (experimental condition) and explicit encoding (EE, control condition) over the course of three visits spaced one week (±2days) apart. All participants were evaluated for recognition 10min after each encoding condition was presented, and again one week (±2days) later. Results indicate that both groups performed better on the EE recognition trials when compared to FM (p's<0.05). For the FM recognition trials, both groups performed similarly. However, participants with schizophrenia performed significantly worse on the EE recognition trials than healthy control participants (p's<0.05). While participants with schizophrenia did not perform significantly worse when assessed for FM recognition, these results do not provide enough evidence to suggest that FM facilitates learning to a greater extent in schizophrenia when compared to EE. Whether FM may benefit a subgroup of patients with schizophrenia remains a focus of further investigation.